The Effectiveness of a Training Program Based on Meichenbaum Model in Reducing the Desire for Drugs and Psychotropic Substances Level Among Addicts. - Al Mukhaini , Jalal; Hamdi, Mohammad Hamdi (Jordan Journal of Educational Sciences, 2017)
This study intended to investigate the effectiveness of a training program based on Meichenbaum model in reducing the level of desire for drug and psychotropic substances among addicts. The sample consisted of (30) addicts who were admitted to the Half Way Houses Center at al Masarra Hospital of psychiatric and neurological diseases in the Sultanate of Oman. The sample distributed randomly into two groups: experimental and control. The experimental group was subjected to a training program consisting of (19) sessions over three months. The control group did not undergo any training program. A measure of desire for drugs was applied pre-, post- and after one month of follow up. Results showed statistically significant difference between the two groups in favor of the experimental group in the level of desire for drugs.There was no significant difference in the desire for drugs between the post- measure and the four weeks follow- up measure among the experimental group